Literacy Policy and Provision in Papua New Guinea - Olsson, Micael ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
There is now consensus among educators in Papua New Guinea that literacy efforts must be strengthened through closer bonding of literacy with information-that-matters. Papua New Guinea's Cabinet has recently endorsed a National Literacy and Awareness Program linking literacy projects with public awareness campaigns, hoping to increase support for literacy by coordinating existing projects and resources, thus reducing unnecessary duplication of costs. Literacy in less developed countries needs national policy but can piggy-back on global concerns over awareness issues for supplementary funding. (Appendixes include a description of the vernacular literacy program, program specifications and management structure for the literacy and awareness program, the Melanesian Accord, and a description of the Landowner Awareness Centre program.) (Author/RS)
ERIC Note: Paper presented at the World Congress on Reading (13th, Stockholm, Sweden, July 3-6, 1990).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Education; Developing Nations; Educational Policy; Elementary Secondary Education; Foreign Countries; Literacy; National Programs; Program Descriptions; Papua New Guinea; Speeches/Meeting Papers; Reports, Descriptive